2015
DOI: 10.1111/fare.12099
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Family Resilience Through Evidence‐based Policy Making: Reconsidering the Link Between Adult–Infant Bedsharing and Infant Mortality

Abstract: Evidence‐based policy making often has a direct or indirect goal of promoting family resilience. The authors consider the ways in which scholarly disagreements about evidence can challenge this goal, focusing on the debate regarding whether adult–infant bedsharing increases the risk of infant mortality. A central issue is whether scholars conclude that public policy should recommend against all bedsharing or only bedsharing in particular risky circumstances. The authors use context‐based evidence‐based policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…The work of anthropologists in shaping policy at the intersection of SIDS and infant sleep location is increasingly being recognized in policy discussions in the United States (e.g., Altfeld et al. ; Gordon, Rowe, and Garcia ; Mileva‐Seitz et al. ) and practice recommendations in the United Kingdom (e.g., UNICEF UK ), and is firmly embedded in policy and practice recommendations addressing breastfeeding initiation and nighttime infant feeding (e.g., Ball and Blair ; Feldman‐Winter and Goldsmith ; Holmes, McLeod, and Bunik ; Rapley ).…”
Section: Transforming the Paradigm: An Integrated Anthropological Appmentioning
confidence: 99%
“…The work of anthropologists in shaping policy at the intersection of SIDS and infant sleep location is increasingly being recognized in policy discussions in the United States (e.g., Altfeld et al. ; Gordon, Rowe, and Garcia ; Mileva‐Seitz et al. ) and practice recommendations in the United Kingdom (e.g., UNICEF UK ), and is firmly embedded in policy and practice recommendations addressing breastfeeding initiation and nighttime infant feeding (e.g., Ball and Blair ; Feldman‐Winter and Goldsmith ; Holmes, McLeod, and Bunik ; Rapley ).…”
Section: Transforming the Paradigm: An Integrated Anthropological Appmentioning
confidence: 99%
“…The resulting misdirection in safe sleep policy may have been overlooked initially as attention was diverted toward controversy concerning the strength of evidence for one aspect of the population-wide recommendation. For example, the recommended total bedsharing ban became a major obstacle to prevention in many countries, including the United States (Middlemiss, Yaure, & Huey, 2014), as research findings supported both (a) bedsharing as a central risk for SIDS and (b) bedsharing as a potentially safe practice contingent on factors addressed by the triple-risk model (Gordon, Rowe, & Garcia, 2015;Vennemann et al, 2012). For example, researchers reported that bedsharing was a statistically higher risk for infants exposed to cigarette smoke than for those not exposed to cigarette smoke (notably, these findings were recently replicated in New Zealand; Mitchell, Cowan, & Tipene-Leach, 2016).…”
Section: Persisting Disparitiesmentioning
confidence: 99%
“…However, the lack of substantial reduction in sleep-related infant deaths despite the prevalence of abstinence-only messages suggests that a strict ABC message with a strong anti–bed-sharing stance may not be the best strategy for reducing overall SIDS/SUID rates and disparities. Bed-sharing behavior, in fact, seems to be quite resistant to change and is often accompanied by other SUID risks (e.g., use of soft bedding and multiple people in bed) that might be more susceptible than bed-sharing itself to intervention (Blabey & Gessner, 2009; Blair, Sidebotham, Berry, Evans, & Fleming, 2006; Gordon, Rowe, & Garcia, 2015). Clearer messaging about the dangers of co-sleeping on couches and similar surfaces is also necessary.…”
Section: Conclusion For Practicementioning
confidence: 99%